Sarthaks Test
0 votes
920 views
in Mathematics by (15.0k points)

Factorise the following expressions

(i) (l + m)2 − 4lm (Hint: Expand (l + m)2 first)

(ii) a4 + 2a2b2 + b4

1 Answer

0 votes
by (24.8k points)
selected by
 
Best answer

(i) (l + m)2 − 4lm 

= l2 + 2lm + m2 − 4lm

= l2 − 2lm + m2

= (l − m)    [(a − b)2 = a2 − 2ab + b2]

(ii) a4 + 2a2b2 + b4 

= (a2)2 + 2 (a2) (b2) + (b2)2

= (a2 + b2)2       [(a + b)2 = a2 + 2ab + b2]

Related questions

0 votes
1 answer
0 votes
1 answer
0 votes
1 answer
0 votes
1 answer

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...